2008
DOI: 10.1177/1524839907306405
|View full text |Cite
|
Sign up to set email alerts
|

BART to HIVEd: Adapting an HIV Education Prevention Program

Abstract: One of the fastest growing segments of the population infected with HIV is the nation's youths. Thus, prevention in this high-risk population is vital. The authors detail the process of adapting an evidence-based HIV/AIDS educational program (HIVEd) to the unique needs of high-risk youths in adjudicated and detained facilities and alternative high schools. The HIVEd program derives from St. Lawrence's Becoming A Responsible Teen (BART) curriculum. This article describes the modification of BART into HIVEd, ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Previous research identified a general belief that New Zealand, as a result of factors such as geographic isolation, reduce the likelihood of a pandemic and thus increase a belief that New Zealand is a relatively safe place to be in the event of a pandemic [4]. Perceived risk was also attenuated by a belief that border control agencies will prevent pandemic flu entering New Zealand, with this possibly resulting in people transferring responsibility for preparing from themselves to border control agencies [6]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research identified a general belief that New Zealand, as a result of factors such as geographic isolation, reduce the likelihood of a pandemic and thus increase a belief that New Zealand is a relatively safe place to be in the event of a pandemic [4]. Perceived risk was also attenuated by a belief that border control agencies will prevent pandemic flu entering New Zealand, with this possibly resulting in people transferring responsibility for preparing from themselves to border control agencies [6]. …”
Section: Resultsmentioning
confidence: 99%
“…It is important to accommodate the fact that disbelief in the effectiveness of measures can result in people failing to act and developing distrust of sources of information [6]. Previous New Zealand research identified a general belief that local agencies will manage a pandemic well and that New Zealand is a relatively safe place to be in the event of a pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with the BART intervention, the HIVEd program (a modified version of the BART intervention) aims to improve adolescent outcomes through the promotion of abstinence and consistent, correct condom use. The HIVEd program targets participants' knowledge, attitudes, and skills, with the overarching goal of influencing positive behavior change (Polacek et al, 2008).…”
Section: Hiv Education (Hived) Prevention Interventionmentioning
confidence: 99%
“…All measures were collected at both baseline and exit interviews. Questionnaire wording was adapted to reflect common expressions of youths (Polacek et al, 2008). The surveys were administered by trained research staff following systematic data collection and questionnaire administration guidelines.…”
Section: Data Collectionmentioning
confidence: 99%